Pelatihan Pembuatan dan Aplikasi “PESTOGANIK” Pestisida berbahan Dasar Tomat Organik - Sumartono, Eko; Afriani, Ririn; Yulihartika, Rika Dwi; Moulina, Methatias Ayu (Damhil: Jurnal Pengabdian kepada Masyarakat, 2025)
This community empowerment program aims to educate residents of Desa IV Suku Menanti on making an organic pesticide called “Pestoganik” from overripe tomatoes and natural ingredients. Pestoganik utilizes bioactive compounds such as tomatine and solanine in tomatoes, combined with garlic, tobacco, lemongrass oil, baking soda, and vinegar. The method involved hands-on training, ingredient demonstrations, and application tests. The solution proved effective in reducing pest populations such as aphids and leaf borers by more than 60% within a week. Additionally, it is low-cost, environmentally friendly, and easy to replicate using local materials. The training not only improved pest management but also raised awareness of sustainable farming practices. This activity demonstrates a simple, community-based solution to reduce dependence on chemical pesticides.